2019
DOI: 10.1126/scitranslmed.aaw1565
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic mRNA nanoparticle-mediated restoration of p53 tumor suppressor sensitizes p53 -deficient cancers to mTOR inhibition

Abstract: Loss of function in tumor suppressor genes is commonly associated with the onset/progression of cancer and treatment resistance. The p53 tumor suppressor gene, a master regulator of diverse cellular pathways, is frequently altered in various cancers, for example, in ~36% of hepatocellular carcinomas (HCCs) and ~68% of non–small cell lung cancers (NSCLCs). Current methods for restoration of p53 expression, including small molecules and DNA therapies, have yielded progressive success, but each has formidable dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
159
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(177 citation statements)
references
References 97 publications
1
159
0
2
Order By: Relevance
“…Obtaining sufficient delivery and intracellular expression will be amongst the most important challenges. Encouragingly, the in vivo delivery of therapeutic mRNA is starting to be realized outside of the vaccine arena [55][56][57][58][59][60] .…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining sufficient delivery and intracellular expression will be amongst the most important challenges. Encouragingly, the in vivo delivery of therapeutic mRNA is starting to be realized outside of the vaccine arena [55][56][57][58][59][60] .…”
Section: Discussionmentioning
confidence: 99%
“…[ 37 , 38 ] Although it is not being widely applied in current antiviral research, its potential is unquestionable. To summarize, the advantages of nanotechnology in antiviral research include the following: 1) promotes the delivery of water-insoluble drugs;[ 39 ] 2) enhances the circulation time of drugs in vivo ;[ 40 ] 3) achieves co-delivery of drugs;[ 40 ] 4) improves drug utilization efficiency and reduce side effects through targeting antibody modification;[ 41 ] 5) protects DNA and mRNA vaccines, overcoming bottlenecks for in vivo applications;[ 42 ] and 6) the physicochemical properties of nanomaterials can also be employed directly against viruses. [ 43 ] In this section, we will focus on the aspects of nanotechnology that have the greatest potential for clinical transformation or that have already been applied in the clinic, including in the delivery of antiviral drugs and vaccines, and the design of nanomaterials directly effective against viruses.…”
Section: Nanotechnology Versus the Virusmentioning
confidence: 99%
“…In recent studies, some antineoplastic agents that can activate p53 pathway have been found in vitro. Cell-cycle arrest and apoptosis of HCC1419 (mutp53-Y220C) can be provoked by SLMP53-2, which is a new molecule to activate mutation of p53 by enhancing its interaction with the heat-shock protein 70 (Hsp70) and leading to the reestablishment of p53 DNAbinding ability as well as wild-type p53 144,145 . In another p53-null HCC line, the cell growth of Hep3B cells can be inhibited by melatonin (a hormone for regulation of circadian rhythms), which can promote the expression of several proapoptotic target genes (p21 and BAX) of p53 146 .…”
Section: Anti-hcc By Restoring P53 Function and Normalizing Mdm2-p53 mentioning
confidence: 99%